1972
DOI: 10.1254/jjp.22.347
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Responses of Isolated Rabbit Aortae to Transmural Stimulation as Affected by Calcium, Strontium, Sodium and Ouabain

Abstract: There are a number of reports describing that not only in visceral (1-3) but also vascular smooth muscles (4-6) Ca++ may be the agent linking membrane excitation to contraction.Increasing [Ca++]0 may either stimulate (7,8) ranging from 0 to 4.4 mM (13).
It seems likely that Sr++ can substitute for Ca++ in the contractile mechanism of skeletal, cardiac and smooth muscles (14-18) and in the release of the neurohumoral trans mitter from sympathetic nerve…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Raising the calcium in the medium to 5 mM increased the responses to field stimulation and norepinephrine. Others have indicated that increasing calcium above the normal range augments adrenergic transmitter release [6,8], whereas T oda [10] found no effect on the responses to transmural stimulation. In our experiments the responses to both field stimulation and norepinephrine were potentiated by raising calcium concentration, which suggests that a postsynaptic effect of cal cium was involved, yet a presynaptic influence cannot be totally ruled out.…”
Section: Discussionmentioning
confidence: 96%
“…Raising the calcium in the medium to 5 mM increased the responses to field stimulation and norepinephrine. Others have indicated that increasing calcium above the normal range augments adrenergic transmitter release [6,8], whereas T oda [10] found no effect on the responses to transmural stimulation. In our experiments the responses to both field stimulation and norepinephrine were potentiated by raising calcium concentration, which suggests that a postsynaptic effect of cal cium was involved, yet a presynaptic influence cannot be totally ruled out.…”
Section: Discussionmentioning
confidence: 96%
“…Potentiation of the strontium-induced contraction by cocaine in a calcium-free solution Strontium has been shown to cause contraction of smooth muscle (Daniel, 1963) and can substitute for calcium in the contraction of smooth muscle (Daniel, 1965;Hudgins, 1969;Toda, 1972). Experiments were done to see if strontium would contract the isolated spleen strip in the absence of extracellular calcium, and whether cocaine would potentiate this response.…”
Section: Resultsmentioning
confidence: 99%
“…Strontium can substitute for calcium in the contraction of smooth muscle (Sperelakis, 1962;Daniel, 1963;Bohr, 1964;Hudgins, 1969), possibly by displacing bound intracellular calcium (Daniel, 1965;Toda, 1972). Our experiments where pretreatment of the cat with reserpine did not reduce the contraction caused by strontium in spleen strips bathed in calcium-free solution indicate that the contraction was not due to the release of stored noradrenaline.…”
mentioning
confidence: 80%
“…The mechanism appears to include both direct vasoconstriction and a neurally mediated effect 7 . Direct vasoconstriction of blood vessels by digitalis has been demonstrated in excised strips of arteries, veins 9–14 and aortas 15,16 …”
Section: Introductionmentioning
confidence: 99%